Comparative Analyses of Physicochemical Properties of Artisanal Refined Gasoline and Regular Automotive Gasoline - Udo, Godwin J.; Awaka-Ama, Joachim J.; Uwanta, Emaime J.; Ekwere, Ifiok O.; Chibueze, Igwe R. (Frontiers in Chemistry, 2020)
Physicochemical properties of Artisanal Refined Gasoline (ARG) and Regular Automotive Gasoline (RAG) sampled from Eastern Obolo Creek and Mkpat Enin, Akwa Ibom Nigeria were investigated. This was to compare the physicochemical properties of the two gasoline samples with each other and their compliance with ASTM standards. The finding revealed Antiknock index of RAG(91.15%) and LRG(83.05%), Atmospheric distillation of RAG(185 oC) and LRG (184oC), Reid Vapor pressure RAG (0.53 kg/cm3)and ARG(0.36 kg/cm3), specific gravity of RAG(0.771) and LRG(0.683), sulfur content of RAG(0.014%/wt) and LRG(0.02%/wt) while Flash point for RAG were Pensky martens -25oC, Abel-Pensky -33 oC and LRG Pensky Martens –27 oC, Abel-Pensky -35.36 oC respectively. The Research octane number, motor octane number, Reid vapor pressure, sulfur content and specific of RAG were ASTM compliance while only final boiling point, and sulfur content of LRG were within ASTM range. Base on the findings, the LRG might have been poorly refined or adulterated and could constitute problems in automotive engines if used. However, this crude technology can be upgraded, the gasoline quality improved through alkylation, isomerization, cyclyzation. Artisanal refiners should be trained and make proficient with intent of incorporating them into upstream petroleum sector.